Implementasi Teknik Modifikasi Perilaku Token Ekonomi Untuk Meningkatkan Minat Baca Siswa Kelas Tk B di TK Islam Mujahidin Surakarta - Tiara Arum Novelinna; Dhian Riskiana Putri; Anniez Rachmawati Musslifah (Pusat Riset dan Inovasi Nasional, 2026)
Early childhood reading interest is an important factor in the development of sustainable literacy skills. However, the reading interest of kindergarten B students at Mujahidin Islamic Kindergarten in Surakarta still needs to be improved to support the quality of learning. The research question in this study is how effective the application of behavior modification techniques with economic tokens is in increasing the reading interest of these students. This study aims to determine the effect of using token economies as positive reinforcement in significantly improving early childhood reading interest. The method used is a qualitative approach with direct observation of kindergarten B students. The results of the study indicate that the consistent implementation of token economy techniques can increase students' enthusiasm, concentration, and independence in reading activities. The active role of teachers in providing support and motivation was crucial in achieving these results. The study's conclusion emphasizes that token economy techniques are an effective and practical strategy for enhancing young children's reading interest.